Beyond Java - Tate, Bruce, 1965- (O'Reilly, 2005)
"In Beyond Java, Bruce Tate gives a fair and honest assessment of what Java has accomplished and why it has been such a powerful tool. He shows the ways in which Java has advanced the art of computer programming. But he also shows where it's holding us back, where Java isn't flexible enough for the tasks at hand, and where political forces are driving the Java platform toward increasing complexity and away from the base that had previously served it so well."--Jacket